Konsep Evaluasi Dalam Pembelajaran - Emeliazola; Supratman Zakir; Darul Ilmi (CV. ALIM'SPUBLISHING, 2024)
Abstract. This article is a theoretical study of the importance of the learning evaluation process. This article was written through library research, namely collecting information that is relevant to the topic or problem that is the object of discussion. The data sources for this research are books, journals, articles related to the topic of the concept of evaluation in learning. Data analysis techniques are reading, studying, analyzing and then concluding. The results of this article provide an important message for teachers or educators to review and re-understand the concept of evaluation, evaluation principles, forms of evaluation, objectives and functions of evaluation, evaluation procedures and techniques, uses and benefits of evaluation.